Trends in HPV cervical and seroprevalence and associations between oral and genital infection and serum antibodies in NHANES 2003–2012. Issue 1 (December 2015) - Brouwer, Andrew; Eisenberg, Marisa; Carey, Thomas; Meza, Rafael
Abstract Background HPV infects multiple sites in the epithelium, including the genitals and oral cavity. The relation between genital and oral infections and serum antibodies can help explain the natural history and epidemiology of HPV. Methods We analyzed HPV data from NHANES derived from self-collected vaginal swabs (women ages 14–59, 2003–12), oral rinses (men and women 14–69, 2009–12), and serum (men and women 14-59, 2003–10). Results Type-concordance of cervicogenital and oral infections in women was found to vary widely by age. Prevalence of oral infections with type-concordant antibodies was low but varied by sex: 0.2 % (95 % CI 0.0–0.8) for women vs 0.8 % (95 % CI 0.4–1.3) for men. Vaccination was associated with a reduced risk of cervicogenital infection for vaccine genotypes among ages 14–17 (0.2 (95 % CI 0.1–0.8)) and 18–24 (0.2 (95 % CI 0.1–0.3). Seroprevalence trends in women showed a dramatic increase for recent birth cohorts, likely due to vaccination. By contrast, trends for men remained relatively constant. Age-specific cervicogenital prevalence showed a consistent peak in the late teens and twenties. Relative cervicogenital prevalence has largely been decreasing since the 1940–50 birth cohort. Conclusions There are complex patterns in HPV prevalence trends and type-concordance across infection sites and serum antibodies. A multisite sampling scheme is needed to better understand the epidemiology and natural history of HPV.